A rapid and efficient analytical method for the quantification of a novel anticholinergic compound, R‐phencynonate, by stable isotope‐dilution LC–MS/MS and its application to bioavailability and dose proportionality studies. (5th February 2017) - Li, Jinglai; Liao, Sha; Wang, Xiaoying; Liu, Qian; Meng, Fei; Zhang, Wenpeng; Zhang, Tianhong; Yang, Cuiping; Song, Xinyi; Luo, Huan; Wang, Juan; Li, Zheng; et al.
Abstract: A rapid, specific and high‐throughput stable isotope‐dilution LC–MS/MS method was developed and validated with high sensitivity for the quantification of R‐ phencynonate (a eutomer of phencynonate racemate) in rat and dog plasma. Plasma samples were deproteinized using acetonitrile and then separated on a C8 column with an isocratic mobile phase containing acetonitrile–water–formic acid mixture (60:40:0.1, v /v/v) at a flow rate of 0.2 mL/min. Each sample had a total run time of 3 min. Quantification was performed using triple quadrupole mass spectrometry in selected reaction monitoring mode with positive electrospray ionization. The method was shown to be highly linear ( r 2  > 0.99) and to have a wide dynamic range (0.1–100 ng/mL) with favourable accuracy and precision. No matrix effects were observed. The detailed pharmacokinetic profiles of R‐ phencynonate at therapeutic doses in rats and dogs were characterized by rapid oral absorption, quick clearance, high volume of distribution and poor absolute bioavailability. R‐ Phencynonate lacked dose proportionality over the oral dose range, based on the power model. However, the area under concentration–time curve and the maximum plasma concentration increased linearly in a dose‐dependent manner in both animal models. The absolute bioavailability of R‐ phencynonate was 16.6 ± 2.75 and 4.78 ± 1.26% in dogs and rats, respectively.